Cultivating of Synodontic Fish Larvae (Synodontic eupterus) with Different Initial Feeds - Sukendi Sukendi; Windarti Windarti; Ridwan Manda Putra; Asep Permana (ECOTONE, 2020)
Fish Larvae Maintenance Research Synodontic (Synodontic eupterus) with Early different Feeding type held from July to August 2018 Synodontic fish hatcheries and the Research Institute for Aquaculture Development of Ornamental Fish Depok, West Java. The purpose of this study was to analyze the type and duration of feeding changes in increasing the growth and survival of synodontic fish larvae to seed size. From the research that has been carried out, the best feed for synodontic fish larvae is obtained giving artemia feed after 3 hatching days, 10 to 40 days given tubifex feed with absolute weight growth values of 0, 3762 grams, weight growth rates daily 15.92%, absolute length growth 19.49 mm, and 95% larval life.